THE EFFECTIVENESS OF PICTURED BILINGUAL DICITONARY COMPARED TO NON-PICTURED BILINGUAL DICTIONARY TO IMPROVE THE VOCABULARY MASTERY OF ELEMENTARY SCHOOL STUDENTS - Setiowati, Novi (ELT Forum: Journal of English Language Teaching, 2013)
This journal is based on an experimental study involving the fourth graders of SDN Jatibarang 01 in the academic year of 2012/2013. The objective of this study is to prove the effectiveness of pictured bilingual dictionary to improve the vocabulary mastery of elementary school students. The study involved two groups of students that were experimental and control groups. During the treatment, students in experimental group used pictured bilingual dictionary, while students in control group used non-pictured bilingual dictionary. The design was pretest-post test design. According to the pretest result that had been analyzed by using t-test formula, there was no significant difference in the vocabulary mastery of both groups (0,095<1,721, df = 21, ? = 5%). However, the post test result showed that the vocabulary mastery of experimental group is significantly different with the vocabulary mastery of control group. It is proven by the result of t-test analysis toward the post test result in which tvalue exceeds ttable (1,911>1,721, df = 21, ? = 5%). As a result, pictured bilingual dictionary is more effective compared to non-pictured bilingual dictionary to improve the vocabulary mastery of elementary school students. Therefore, I suggest the students to have pictured bilingual dictionaries compared to non-pictured bilingual ones. I also suggest the institution to equip the school library with pictured bilingual dictionaries to ease the students get the dictionaries and to facilitate the English learning process.